Optical modelling of P3HT: PC 71 BM semi-transparent organic solar cell - Upama, M.; Wright, M.; Elumalai, Naveen Kumar; Mahmud, M.; Wang, D.; Chan, K.; Xu, C.; Haque, F.; Uddin, A. (Springer, 2017)
The optical properties of a novel semi-transparent organic solar cell were investigated both experimentally and by transfer matrix modelling to maximize photocurrent generation. The effect of multilayer anode thickness and illumination direction was studied. Bottom illumination was shown to provide enhanced exciton generation and increased photocurrent. Changing the multilayer anode thickness also influenced the device reflectance and photocurrent generation.